Stroke unit and Neurocritical Care Unit for acute neurological diseases in the USL Toscana Centro: a pilot model of Santo Stefano Hospital in Prato - Valenti, Raffaella; Caruso, Alba; Scotto Di Luzio, Anita E.; Accavone, Donatella; Cagliarelli, Maria G.; Chiti, Guido; Grassi, Enrico; Briccoli Bati, Maria; Palumbo, Pasquale (Frontiers in Stroke, 2023)
Background Acute neurological diseases are leading causes of disability and death. The need for specialist neurocritical care skills for managing neurological emergencies has increased. Promising opportunities exist to improve outcomes in acute phases of neurological diseases, such as, for example, the concept of a stroke unit for stroke patients. A similar concept was introduced for a neurocritical care unit, which is associated with improved clinical outcomes compared with more traditional management. However, neurocritical care is often not recognized as a separate specialty. Significant progress in neurology has enabled better approaches for the critically ill neurologic patient, in particular those with stroke and hemorrhage, but also with epileptic seizures and epileptic status, traumatic brain injury (TBI), subdural/epidural hematoma, acute inflammatory polyradiculoneuritis, encephalitis, myasthenia gravis, acute myelitis, etc. Assessment of policy/guidelines options and implications Except for cerebrovascular diseases, for other acute neurological diseases, there is no standardized model care service recognized. A good patient outcome can be obtained by the choice of neurology setting for acute patients including nursing and medical staff with specific training in neurocritical care. As we believe neurocritical care practices should be implemented, we suggest a pilot model on the basis of our experience. In this report, we show a model of the 2A setting of the Santo Stefano Hospital (Prato, USL Toscana Centro), where, as well as stroke units for cerebrovascular events, we have neurocritical care unit and acute-neurology experts for all acute neurological diseases. Actionable recommendations: our pilot experience The 2A setting of Stroke Unit/Neurocritical Care of the Santo Stefano Hospital includes 15 beds; 8 ± 2 beds are monitored by portable multi-parameter monitoring devices. Following acute treatment, diagnostic/etiologic work-up and automated monitoring of vital functions are performed in addition to adapted secondary prevention, early rehabilitation, and prevention of complications in all acute patients. We retrospectively assessed the diagnoses in the hospital discharge forms (HDF) of Stroke Unit/Neurocritical Care (2A) of 249 patients consecutively analyzed between 1 January 2022 and 30 June 2022. Out of the 249 patients affected by acute neurological diseases, 155 had cerebrovascular diseases (62.2%). In particular, 100 (64.5%) were diagnosed with ischemic stroke and 44 (28.4%) with hemorrhagic stroke. Thirty-two patients (12.8%) were hospitalized following a TBI. Sixteen patients (6.4%) had a new diagnosis of epilepsy and three (1.2%) of epileptic status. In our setting, the 3-month modified Rankin Scale (mRS) in the 36 stroke patients treated with recombinant-tissue plasminogen activator (r-TPA) was 0–2 (low disability) in 60% of cases. Additionally, 31% of 44 intracerebral haemorrhage (ICH) patients reported a moderate-severe degree of disability. Regarding TBI patients, the mRS ranged from 1 to 5, with significate difference between patients in Stroke Unit/Neurocritical Care (2A) in comparison with those in other departments (2–3 vs. 3–4, respectively). Globally, the setting discharge of the acute neurological patients were: rehabilitation (26%), intermediate care hospitals (44%), long-term care (5%), and home (25%). The 1-month mortality rate was 1.8%. Discussion We provide a brief description of the cases treated over a 6-month period to draw attention to the possibility of the existence of a ward dedicated exclusively and specifically to all acute neurological diseases. The sample of patients is very varied and interesting. More than 60% of patients had cerebrovascular diseases. The paucity of outcome data makes this report limited, but the diagnostic-therapeutic strategies, the presence of staff trained in specific neurocritical care, and the use of inpatient hospital-based registries are, in our opinion, strengths. Our pilot model of the setting of Stroke Unit/Neurocritical Care (2A) in the Santo Stefano Hospital (Prato, USL Toscana Centro) should be further implemented, also to verify systematically the associations with measurable outcome improvements in patients affected by strokes and other neurological acute diseases.